1985
DOI: 10.1080/14640748508401173
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Relational Rules in Matching and Oddity Learning by Pigeons and Corvids

Abstract: Three experiments compared the performance of pigeons and corvids when they were given the opportunity to transfer the relational rule underlying matching or oddity discriminations to new sets of stimuli. In the first, pigeons and jackdaws were initially trained either on a matching or on a non-relational conditional discrimination and then transferred to a new matching discrimination. In the second, pigeons and jays were trained on a series of three matching (or oddity) discriminations with three different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
1
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 22 publications
2
68
1
2
Order By: Relevance
“…For example, in Experiment 3 in Wilson et al (1985), pigeons received S/D training in which two response keys were simultaneously lit with two identical colors (mauve-mauve or blue-blue) or with two different colors (mauve-blue or blue-mauve). Reinforcement was given for pecking one key (e.g., left) when the colors were the same and the other key when they differed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Experiment 3 in Wilson et al (1985), pigeons received S/D training in which two response keys were simultaneously lit with two identical colors (mauve-mauve or blue-blue) or with two different colors (mauve-blue or blue-mauve). Reinforcement was given for pecking one key (e.g., left) when the colors were the same and the other key when they differed.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nonprimate species tested, only a few birds, such as parrots (Pepperberg, 1987) and corvids (Wilson et al, 1985), and cetaceans, such as dolphins (Herman, Pack, & Morrel-Samuels, 1993;Mercado, Killebrew, Pack, Macha, & Herman, 2000), appear to transfer two-item S/D discriminations to novel stimuli. This reliance on more complex, multiitem displays raises the issue of whether the pigeons are performing the S/D discrimination in the same way as primates.…”
mentioning
confidence: 99%
“…Finally, corvids are proficient in transferring to novel stimuli in matching and oddity discriminations. Rooks, jays, and jackdaws outperform pigeons on these problems (51). What is common to these various transfer tasks-from learning sets to transitive inference-is the ability to abstract general rules or relationships that transcend the basic learning experience.…”
Section: Wwwsciencemagorg Science Vol 306 10 December 2004mentioning
confidence: 99%
“…When presented with a series of different discriminations to learn, corvids (blue jays, rooks, jackdaws, and Eurasian jays), like monkeys and apes, extract the general rule, such as win-stay, lose-shift rather than having to learn each new discrimination afresh. By contrast, pigeons appeared to be rote learners, solving the task eventually by learning each discrimination individually (50,51).…”
Section: Wwwsciencemagorg Science Vol 306 10 December 2004mentioning
confidence: 99%
“…The proposal that, for pigeons, conditional cues are more salient than identity/difference cues does not imply that pigeons show peculiar difficulty (relative, for example, to individuals of other species) in using identity/ difference as a cue. Wilson, Mackintosh, and Boakes (1985b), for example, found that jackdaws (Corvus monedula), unlike pigeons, learned an MTS task more rapidly following previous MTS training (with different stimuli) than following training in a conditional task. The jackdaws, then, achieved relational learning in the initial MTS task.…”
Section: Discussionmentioning
confidence: 99%